Virtual Expo Pengenalan Produk Dalam Negeri Berbasis Web - Muhammad Iqbal Wardana; Wardana, Muhammad Iqbal; Adi Susilo, Anang Kukuh (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2022)
Virtual Expo is an online-based virtual exhibition platform and as a substitute for physical exhibition, because the current pandemic era is a very difficult era, especially in the field of introducing domestic products produced by UMKM, due to the limitations of UMKM to be able to physically exhibit such as inside buildings. To overcome this problem, this research was carried out using a web-based virtual expo system. In this research 2D and 3D graphics are used as a feature to introduce UMKM products, with the user as a admin and the owner products of the virtual expo. Products owner are expected to be able to place their products on the system and admin can add products display. The research method used to complete this research starts from making functional and non-functional requirement analysis, system design, web design, virtual exhibition, environment design, 3D objects, material, assets, implementation and testing. The results achieved in this research is a virtual exhibition that can help introduce UMKM products that are made, so that people are easier and more interested using the system on the user and the costumer side.